Analysis of directions for overcoming the difficulties of warehousing while ensuring logistics processes - Maria Naumenko (ScienceRise, 2019)
In article the analysis of commodity flows according to logistics features is considered, special attention is given to the study of the nomenclature list of goods with division by product groups and type. The study of alternative design of logistic flows is performed, which recommended the use of three-dimensional ABC-XYZ-DEF analysis. The analysis of the difficulties and possible risks of making internal warehouse technological decisions is made, which is considered on the example of the design of warehouses’ floors